2007
DOI: 10.1037/0033-2909.133.3.419
|View full text |Cite
|
Sign up to set email alerts
|

Overgeneral autobiographical memory and traumatic events: An evaluative review.

Abstract: Does trauma exposure impair retrieval of autobiographical memories? Many theorists have suggested that the reduced ability to access specific memories of life events, termed overgenerality, is a protective mechanism helping attenuate painful emotions associated with trauma. The authors addressed this question by reviewing 24 studies that assessed trauma exposure and overgenerality, examining samples with posttraumatic stress disorder, acute stress disorder, depression, traumatic event exposure, and other clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
268
5
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(296 citation statements)
references
References 79 publications
21
268
5
2
Order By: Relevance
“…Van Vreeswijk and de Wilde, 2004;Williams and Broadbent, 1986]. One hypothesis to explain the overgeneral memory effect is that specific memories are avoided because of their negative emotional quality [Moore and Zoellner, 2007;Williams, 1996]. Possibly the two task conditions have different effects on the avoidance of negative memories.…”
Section: Discussionmentioning
confidence: 97%
“…Van Vreeswijk and de Wilde, 2004;Williams and Broadbent, 1986]. One hypothesis to explain the overgeneral memory effect is that specific memories are avoided because of their negative emotional quality [Moore and Zoellner, 2007;Williams, 1996]. Possibly the two task conditions have different effects on the avoidance of negative memories.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8] A similar pattern of retrieval has been observed in individuals with depression, suicidal ideation, and PTSD. In individuals with suicidal ideation, the deficit has been linked to deficits in key areas of future-related cognitive functioning (for review see [9,10] ). For example, Williams et al [11] presented overdose patients with an autobiographical memory task and a future imaginings task.…”
Section: Introduction Complicated Grief (Cg) (Alternately Know Asmentioning
confidence: 99%
“…The first two questions pertain to global aspects of autobiographical remembering. First, as outlined above, difficulties in providing specific memories has been found to be associated with, and predictive of, PTSD (Moore & Zoellner, 2007). Research has demonstrated that specific autobiographical memories of personal unique experiences are emphasized in individualistic cultures as they function to differentiate the self from others and thus, contribute to the independent self-construal (Jobson, 2009b;Ross & Wang, 2010;Wang, 2001;Wang, 2009;Wang & Conway, 2004).…”
Section: Culture and The Remembering Of Traumamentioning
confidence: 99%
“…Instead PTSD sufferers tend to retrieve categoric overgeneral memories (OGM) (i.e. memories for collections of events) (see Moore & Zoellner, 2007;Williams et al, 2007). Another example of a global autobiographical memory difficulty relates to memories of experiences that significantly reflect and inform one's identity.…”
Section: Culture and The Remembering Of Traumamentioning
confidence: 99%